Mazzucato, Mariana, The Entrepreneurial State: Debunking Public vs. Private Sector Myths - Daniel Díaz Fuentes (H-Industri@)
Mazzucato, Mariana, The Entrepreneurial State: Debunking Public vs. Private Sector Myths, Londres, Anthem Press, 2013 (266 págs.), ISBN 9780857282521.